NADPH oxidases differentially regulate ROS metabolism and nutrient uptake under cadmium toxicity. (1st April 2016) - Gupta, D. K.; Pena, L. B.; Romero‐Puertas, M. C.; Hernández, A.; Inouhe, M.; Sandalio, L. M.
Abstract: The role of NADPH oxidases under cadmium (Cd) toxicity was studied using Arabidopsis thaliana mutants AtrbohC, AtrbohD and AtrbohF, which were grown under hydroponic conditions with 25 and 100 μM Cd for 1 and 5 days. Cadmium reduced the growth of leaves in WT, AtrbohC and D, but not in AtrbohF . A time‐dependent increase in H2 O2 and lipid peroxidation was observed in all genotypes, with AtrbohC showing the smallest increase. An opposite behaviour was observed with NO accumulation. Cadmium increased catalase activity in WT plants and decreased it in Atrboh mutants, while glutathione reductase and glycolate oxidase activities increased in Atrboh mutants, and superoxide dismutases were down‐regulated in AtrbohC . The GSH/GSSG and ASA/DHA couples were also affected by the treatment, principally in AtrbohC and AtrbohF, respectively. Cadmium translocation to the leaves was severely reduced in Atrboh mutants after 1 day of treatment and even after 5 days in AtrbohF . Similar results were observed for S, P, Ca, Zn and Fe accumulation, while an opposite trend was observed for K accumulation, except in AtrbohF . Thus, under Cd stress, RBOHs differentially regulate ROS metabolism, redox homeostasis and nutrient balance and could be of potential interest in biotechnology for the phytoremediation of polluted soils. Abstract : Under cadmium stress, respiratory burst oxydase homologs (RBOHs) differentially regulate H2 O2 production, with RBOHC being the most important source of reactive oxygen species; anti‐oxidative defences are also differentially regulated, with superoxide dismutase regulation by RBOHC, as well as the regulation of redox‐couple GSH/GSSG ratio by RBOHC and D and the ASA/DHA by RBOHF being the most important factors. Our results also suggest that RBOHs can play an important role in regulating the root‐to‐shoot nutrient transport and are important players in the nutrient regulatory hub and, for instance, can be of potential interest in biotechnology to protect shoot from heavy metals.